Prevalence and determinants of insulin resistance in recovered COVID-19 and uninfected residents of two regional capitals in Ghana: An observational study. - Ansumana Sandy Bockarie; Leonard Derkyi-Kwarteng; Jeffrey Amankona Obeng; Richard Kujo Adatsi; Ebenezer Aniakwaa-Bonsu; Charles Apprey; Jerry Ampofo-Asiama; Samuel Acquah (PLOS Global Public Health)
The long-term impact of the coronavirus disease 2019 (COVID-19) pandemic on metabolic risk factors in different populations has not been fully investigated. Insulin resistance (IR) is a cardinal risk factor for the development of type 2 diabetes mellitus. The current study sought to determine the prevalence and determinants of insulin resistance in selected Ghanaians with and without past COVID-19 status in the Cape Coast and Tamale metropolitan areas. Using a cross-sectional study design involving 510 adult participants, body mass index (BMI), waist-to-hip ratio, systolic blood pressure, lipid profile, insulin, plasma glucose, C-reactive protein (CRP), beta-cell function and insulin resistance levels were measured and compared between participants with and without past COVID-19 status. IR was determined by the homeostatic model (HOMA-IR) and the triglyceride-glucose index (TyG). Percentage prevalence and Poisson regression with prevalence ratio and 95% confidence intervals were applied. IR prevalence ranged from 70.69% to 79.09% (HOMA-IR) and 88.62% to 90.91% (TyG) respectively for Tamale and Cape Coast residents. IR prevalence values of 70.98% and 88% (HOMA-IR) and 89.02% and 90.2% (TyG) for without and with past COVID-19 groups respectively were observed. Irrespective of background, low (31.18%) and high (19.41%) levels of beta-cell function were detected. Additionally, high levels of very-low density lipoprotein cholesterol (8.31%), triglycerides (24.9%), total cholesterol (27.45%), low-density lipoprotein cholesterol (44.71%) and low level of high-density lipoprotein cholesterol (11.96%) coupled with low-grade inflammation (50.59%) were observed. Irrespective of surrogate marker used or past COVID-19 status, age, educational level and triglycerides could significantly associate with IR. With HOMA-IR, fasting plasma glucose, insulin and total cholesterol predicted IR in participants without prior COVID-19 status. With TyG, age, BMI, triglycerides and CRP were the predictors of IR in participants with past COVID-19 status. The risk of development of type 2 diabetes mellitus through insulin resistance is high in our setting. Measures to reduce the rising pace of IR are urgently needed in our setting.